Dampening of CD8+ T Cell Response by B Cell Depletion Therapy in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 4 (8th March 2019) - Néel, Antoine; Bucchia, Marie; Néel, Mélanie; Tilly, Gaelle; Caristan, Aurélie; Yap, Michele; Rimbert, Marie; Bruneau, Sarah; Cadoux, Marion; Agard, Christian; Hourmant, Maryvonne; Godmer, Pascal; et al.
Abstract : Objective: To compare the effects of rituximab (RTX) and conventional immunosuppressants (CIs) on CD4+ T cells, Treg cells, and CD8+ T cells in antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Methods: A thorough immunophenotype analysis of CD4+, Treg, and CD8+ cells from 51 patients with AAV was performed. The production of cytokines and chemokines by CD8+ T cells stimulated in vitro was assessed using a multiplex immunoassay. The impact of AAV B cells on CD8+ T cell response was assessed using autologous and heterologous cocultures. Results: CD4+ and Treg cell subsets were comparable among RTX‐treated and CI‐treated patients. In contrast, within the CD8+ T cell compartment, RTX, but not CIS, reduced CD45RA+CCR7– (TEMRA) cell frequency (from a median of 39% before RTX treatment to 10% after RTX treatment [ P < 0.01]) and efficiently dampened cytokine/chemokine production (e.g., the median macrophage inflammatory protein 1α level was 815 pg/ml in patients treated with RTX versus 985 pg/ml in patients treated with CIs versus 970 pg/ml in those with active untreated AAV [ P < 0.01]). CD8+ T cell subsets cocultured with autologous B cells produced more proinflammatory cytokines in AAV patients than in controls (e.g., for tumor necrosis factor–producing effector memory CD8+ T cells: 14% in AAV patients versus 9.2% in controls [ P < 0.05]). In vitro disruption of AAV B cell–CD8+ T cell cross‐talk reduced CD8+ T cell cytokine production, mirroring the reduced CD8+ response observed ex vivo after RTX treatment. Conclusion: The disruption of a pathogenic B cell/CD8+ T cell axis may contribute to the efficacy of RTX in AAV. Further studies are needed to determine the value of CD8+ T cell immunomonitoring in B cell–targeted therapies.